PENGEMBANGAN MODUL MATEMATIKA MENGGUNAKAN PENDEKATAN PMRI PADA MATERI SPLDV UNTUK SISWA KELAS VIII SMP MUHAMMADIYAH KUPANG - St. Muthmainnah Yusuf; Siti Istiana Ema Beleng (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2020)
This study aims to produce a mathematical module of the material system of two variable linear equations for class VIII semester I with PMRI approach, knowing the quality and effectiveness of the module, as well as the responses of material experts and students about the use of modules in learning. This type of research is development research. Using a 4-D (Four D) model, namely defining, design, development, and dissemination. The subjects in this study were students of VIII grade Muhammadiyah Kupang. The instrument used in this study was the validation sheet evaluation of module validity by material and media experts to measure the module validity and student response questionnaire. The results of the module validity assessment by the material and media experts, based on the results of the module quality assessment by the experts, obtained an average of 3.13 content eligibility aspects with 'valid' criteria, a feasibility aspect of 3.21 presentation with a 'valid' criterion, 3.07 language aspects with 'valid' criteria and PMRI 3.54 aspects with 'very valid' criteria. So overall the results of the media and material expert assessment on the